Restoration Of Hazy Data Based On Spectral And Statistical Methods - Saiful Bahari, Nurul Iman; Ahmad, Asmala; Mohd Aboobaider, Burhanuddin; Razali, Muhammad Fahmi; Sakidin, Hamzah; Mohamad Isa, Mohd Sa'ari (Asian Research Publishing Network (ARPN), 2016)
-